Elimination of phenol by sonoelctrochemical process utilizing graphite, stainless steel, and titanium anodes: optimization by taguchi approach - Nsaif, Hind Jabbar; Majeed, Najwa Saber; Salman, Rasha H.; Abed, Khalid M. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Phenol is one of the worst-damaging organic pollutants, and it produces a variety of very poisonous organic intermediates, thus it is important to find efficient ways to eliminate it. One of the promising techniques is sonoelectrochemical processing. However, the type of electrodes, removal efficiency, and process cost are the biggest challenges. The main goal of the present study is to investigate the removal of phenol by a sonoelectrochemical process with different anodes, such as graphite, stainless steel, and titanium. The best anode performance was optimized by using the Taguchi approach with an L16 orthogonal array. the degradation of phenol sonoelectrochemically was investigated with three process parameters: current density (CD) (25, 50, 75, and 100 mA/cm2), time (1, 2, 3, 4 h), and phenol concentration (100, and 200 mg/l). Signal-to-noise (S/N) ratio and analysis of variance (ANOVA) were utilized to examine the impact of each factor. The optimal conditions for phenol removal were 100 mA/cm2, 100 mg/l of phenol, and 4 hours of electrolysis. Under optimal operating conditions, the phenol removal efficiency was 80.99%. The CD was the most influential factor on phenol elimination effectiveness, while the phenol concentration had the least impact.